Acute atorvastatin is hepatoprotective against ischaemia‐reperfusion injury in mice by modulating eNOS and microparticle formation. (7th April 2015) - Ajamieh, Hussam; Farrell, Geoffrey C.; McCuskey, Robert S.; Yu, Jun; Chu, Eagle; Wong, Heng‐Jian; Lam, Wesley; Teoh, Narci C.
Abstract Background & Aims Steatosis accentuates the severity of hepatic ischaemia‐reperfusion injury (IRI); 'statins' (HMG‐CoA reductase inhibitors) protect the heart and brain against post‐ischaemic injury. We tested whether short‐term administration of atorvastatin protects fatty livers in obese mice against IRI. Methods Mice with dietary or genetic simple steatosis (SS) or non‐alcoholic steatohepatitis (NASH) were subjected to 60 min partial hepatic ischaemia/24 h reperfusion. Atorvastatin was injected intravenously (5 mg/kg) 1 h before IRI. Liver injury, Toll‐like receptor‐4 (TLR4), cytokines/chemokines, iNOS/eNOS expression, eNOS activity and thromboxane B2 (TXB2) production were determined. Results Ischaemia‐reperfusion injury was exaggerated by two‐ to five‐fold in SS and NASH compared with lean liver. Atorvastatin pretreatment conferred 70–90% hepatic protection in all animals. Atorvastatin increased post‐ischaemic eNOS mRNA/protein and strikingly enhanced eNOS activity (by phospho‐eNOS). It also attenuated microparticle (MP) production, NF‐κB activation, significantly dampened post‐ischaemic thromboxane B2 production, induction of TNF‐α, IL‐6, MIP‐1a, MCP‐1, GM‐CSF and vascular cell adhesion molecule‐1 (VCAM), with a resultant reduction on macrophage and polymorphonuclear neutrophil recruitment. Up‐regulation of HMGB1 and TLR4 after IRI was marked in fatty livers; 1 h pretreatment with atorvastatin reduced HMGB1 and TLR4 expression in all livers. Conclusions Acute (1 h) atorvastatin administration is highly hepatoprotective against IRI in NASH, fatty and lean livers. Key mechanisms include suppression of inflammation by prevention of NF‐κB activation, microvascular protection via eNOS activation and suppression of TXB2 and MP release. Short‐term intravenous statin treatment is a readily available and effective preventive agent against hepatic IRI, irrespective of obesity and fatty liver disease, and merits clinical trials in at‐risk patients.